Como são valorizados fatores de bom prognóstico de parto pélvico vaginal por médicos de Ginecologia e Obstetrícia? - Cruz,Joana (2017)
Overview and aims: Caesarean section has been considered the optimal mode of delivery for breech presentations, but in selected cases breech vaginal delivery (BVD) may be acceptable. The aim of this study was to evaluate the importance attributed by obstetricians and gynecologists (ObGyns) to a set of good prognostic factors for BVD. Study Design: Cross-sectional study Population: Specialists and residents of Obstetrics and Gynecology from two hospitals with advanced perinatal support. Methods: Fifteen good prognostic factors for BVD were scored by ObGyns, according to a 5-point Likert scale (5=maximum clinical relevance). Medians and interquartile ranges were calculated and the Mann-Whitney test was used to compare ObGyns with experience with <15 versus ≥15 BVD. Results: Of the 58 participants, 74.1% were specialists but only 34.4% had experience with ≥15 BVD. Twelve of the 15 good prognostic factors were scored with a median of 4, while two factors (>10 years of experience in BVD and training in fetal head extraction with forceps) obtained a median of 5 and one (maternal pelvis imaging evaluation) a median of 2. The main differences between more or less experienced ObGyns was in the importance given by the former to training with simulators (p=0.006) and existence of internal protocol for BVD assistance (p= 0.032). Conclusion: Most good prognostic factors for BVD were well scored by ObGyns, but it is disturbing that the two most scored ones (experience in BVD assistance and training in fetal head extraction with forceps) represent areas with reported low levels of experience among us